Selection wages and discrimination - Ekkehart Schlicht (Economics: The Open-Access, Open-Assessment E-Journal, 2010)
Applicants for any given job are more or less suited to fill it, and the firm will select the best among them. Increasing the wage offer attracts more applicants and makes it possible to raise the hiring standard, thereby improving the productivity of the staff. Wages that optimize on the trade-off between the wage level and the productivity of the workforce are known as selection wages. As men react more strongly to wage differentials than females, the trade-off is more pronounced for men and a profit-maximizing firm will offer a higher wage for men than for women in equilibrium. The argument is not confined to issues of sex discrimination; rather it is of relevance for all labor markets where labor heterogeneity is important and supply elasticities vary systematically across occupations.
Keywords: J31; J7; B54; D13; D42; 330; Discrimination; sex discrimination; occupational discrimination; regional discrimination; selection wages; efficiency wages; hiring standards; monopsony; employment criteria; wage posting; Reder competition; wage structure; inter-industry wage structure; employer size-wage effect; occupational wage structure; Arbeitsnachfrage; Lohnstruktur; Lohndifferenzierung; Effizienzlohn; Monopson; Männer; Theorie